A robust L1 controller design for continuous-time TS systems with persistent bounded disturbance and actuator saturation. (November 2016) - Vafamand, Navid; Asemani, Mohammad Hassan; Khayatiyan, Alireza
Abstract: This paper proposes a novel approach for L1 performance controller design of saturated input nonlinear systems described by Takagi-Sugeno (TS) fuzzy systems. The proposed method utilizes parallel distributed compensation (PDC) approach to minimize the effect of persistent bounded disturbances on the system output and the design conditions are formulated in terms of linear matrix inequalities (LMIs) and a generalized eigenvalue problem (GEVP). The novelty of this paper is to design a saturated robust L1 PDC controller whose procedure comprises new techniques for both minimizing the L1 performance gain and handling actuator saturation constraint. These techniques lead to less conservative results compared to recently published papers in the viewpoint of L1 performance criterion gain as well as the control input saturation. The advantages of the proposed approach in each above-mentioned viewpoint are shown via numerical examples by comparing our results with the existing literatures. Finally, a nonlinear electromagnetic suspension (EMS) system is considered to verify the applicability and efficiency of this novel design method.